Uncertainty about Economic Policy and Decisions to Engage in Real Earnings Management: Evidence from Indonesia’s Capital Market - Januarsi, Yeni; Taufik, H. E. R.; Akhmadi (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: This study examines whether economic policy uncertainty (EPU) influences managers’ choice to engage in real earnings management (EM) in the Indonesian capital market. Background Problems: As a major driver of aggregate economic growth and business cycles, EPU may induce information asymmetry, affect the quality of financial reporting, and raise concerns about how macroeconomic conditions may impact how managers behave in managing reported accounting numbers. Novelty: This study explains how the lean against the wind theory and the lean with the wind theory affect real EM behavior in emerging markets. In addition, this study considers the endogeneity problem, which has frequently been overlooked in similar studies, and provides a robust analysis utilizing a variety of tests to validate the proposed hypothesis. Research Methods: This study investigates 1,800 firm-year observations represented by 200 Indonesian publicly listed firms from all industries that have data available, except the banking and financial industries, from 2012 to 2020.The researchers employ time-series cross-sections, pooled ordinary least squares (OLS),and robust standard errors clustered by years. Finding/Results: EPU causes managers to engage in more real EM. This result holds for a series of robustness tests, including testing by using a presidential election for alternative measurements for EPU. From additional analysis, this study reveals that the effect of EPU on real EM is more significant for more profitable firms. Conclusion: This study supports the lean against the wind theory for emerging markets. This evidence implies that EPU conditions induce managers to engage in more real earnings management in emerging market firms, and the uncertain environment can reduce the quality of financial information .